30-Day Readmission After Spine Surgery: An Analysis of 1400 Consecutive Spine Surgery Patients. Issue 7 (1st April 2017) - Adogwa, Owoicho; Elsamadicy, Aladine A.; Han, Jing L.; Karikari, Isaac O.; Cheng, Joseph; Bagley, Carlos A.
Abstract : Study Design: Retrospective cohort review. Objective: To identify the rates, causes, and risk factors for 30-day unplanned readmissions in after elective spine surgery at our institution. Summary of Background Data: Early readmission after spine surgery is being used as a proxy for quality of care. One-fifth of patients are rehospitalized within 30 days after spine surgery. Nearly 60% of these readmissions are unplanned, which translates into billions of dollars in healthcare costs. Methods: A total of 1400 patients undergoing elective spine surgery at Duke University Hospital between 2008 and 2010 were included in the study. We identified all unplanned readmissions within 30 days of discharge. Unplanned readmissions were defined to have occurred as a result of either a surgical or a nonsurgical complication. Patient records were reviewed to determine the cause of readmission and the length of hospital stay. Results: A total of 132 (9.4%) unplanned early readmissions were identified. The mean ± SD age was 58.6 ± 15.1 years. Lumbar decompression and fusion was the most common procedure The most common causes for readmission were infection or a concern for infection (34.8%) and pain (19.7%), and 26.5% of readmissions required a return to the operating room. The majority of patients that were readmitted presented to the emergency department from home (58.0%) whereas 25.2% were readmitted from a skilled nursing facility. The mean ± SD number of days from discharge to readmission was 9.8 ± 7.9 days and the average length of hospital stay for the readmissions was 7.5 days. Conclusion: This study suggests that infection and refractory pain were the most common primary reasons for unplanned readmission. Efforts at reducing unplanned early readmission after elective spine surgery should be focused on more effective post discharge care. Level of Evidence: 3